Association between type and level of disability with overweight of obesity among the disabled in Kelantan - Ismail, Nor Faizah (2020)
Background: People with disabilities are vulnerable to a disability-related health condition, especially non-communicable diseases. They had an issue in psychosocial and physical, which caused limitation in participating in physical activity, leading to increased risk for overweight or obese. This condition will double the burden to themselves, family, and healthcare. To our knowledge, there is yet no analytical study done looking at the association between type and level of disability with obesity or overweight in Malaysia. Objective: This study aims to describe the prevalence of obesity and overweight among the disabled in Kelantan and determine the association between type and level of disability with obesity or overweight among the disabled in Kelantan. Methodology: A cross-sectional study was conducted from March 2020 till May 2020 involving ten districts in Kelantan. The study used secondary data derived from Borang Permohonan Pendaftaran Orang Kurang Upaya BPPOKU (Pindaan 1/2012) form as the source of data. All the selected variables, as documented in the form, were collected. Simple logistic and multiple logistic regression analyses were used to analyse the association between type and level disability with obesity or overweight. Result: A total of 164 subjects who fulfill the inclusion and exclusion criteria were studied. This study revealed that 33.6% of the residents were obese or overweight. Further analysis showed that learning disability was significantly associated with obesity/overweight (Adj. OR 0.132, 95% CI; 0.05,0.35; p=<0.001). Only age was found significantly associated with obesity/overweight (Adj. OR 1.047, 95% CI; 1.01, 1.09; p= 0.019) for the cofounder. Conclusion: We found that those with a learning disability had less probability of being overweight/obese as compared to other types of disability. However, increasing age will increase the risk to get obesity or overweight. Being able to recognize groups at risk to become obese/overweight will undoubtedly help us optimize the control and prevention programme to reduce secondary health disease burden among the disabled, specifically obesity them, in Malaysia, especially in Kelantan.